Administrative Decisions at Creation of Optimum Trajectories of a Financial Stream on the Separate Insurance Contract - Svetlana Alexandrovna Kalaida (Управленческое консультирование, 2018)
Article is devoted to making management decisions aimed at organizing the optimal trajectory of the financial flow under the insurance contract . Management of financial flows for an individual insurance contract is considered as one of the opportunities to improve the efficiency of the entire activity of the insurer. Under the effective activity of the insurer in the study refers to activities aimed at making a profit while guaranteeing the performance of insurance liabilities. The optimum trajectory involves the implementation of the main objectives of the insurer in respect of the insurance contract - performance of insurance liabilities under the contract and receipt for it, depending on the insured event the best possible financial result. Financial flow movement along such atrajectory would mean the effective passage of the insurance contract. The insurer should take certain management decisions to ensure optimal cash flow trajectory. We examined the possibility of obtaining the best financial result for the individual insurance contract in the development of management decisions. The article defines the conditions to ensure the implementation of insurance liabilities due to adequacy of insurance reserves and own funds, as well as the conditions for obtaining the highest possible positive result of the financial flow of the insurance contract. To perform each of the conditions set out to construct the corresponding managerial decisions at the level of the insurer. It was built tree of management decisions, which reflects the interdependence and sequence of implementation of these decisions. Adoption of the proposed management decisions on a separate insurance contract will increase the effectiveness of the insurance company as a whole.